Nationalism and Rationality - Michael Hechter (Journal of World-Systems Research, 2015)
Recent years have witnessed a virtual epidemic of nationalist violence in the world. In 1994, for example, eighteen of the twenty-three wars being fought were based on nationalist or ethnic challenges to states. About three quarters of the worlds refugees were ?eeing from, or were displaced by, ethnic or nationalist con?icts. And eight of the thirteen United Nations peacekeeping operations were designed to separate the protagonists in ethnopolitical con?icts.